Violence against children during COVID-19: Assessing and understanding change in use of helplines - Petrowski, Nicole; Cappa, Claudia; Pereira, Andrea; Mason, Helen; Daban, Rocio Aznar (Child abuse & neglect, 2021)
Many of the measures taken by countries to contain the spread of COVID-19 have resulted in disruptions to child protection services. Despite this, many countries have worked to ensure that child helplines remain operational, making such mechanisms even more critical for reporting and referring cases of violence and for providing support to victims. The purpose of this paper is to document what has occurred, and been reported, to child helplines during the COVID-19 pandemic. The study entailed primary data collection from child helplines and a search of media articles and news stories. Child helplines submitted data on the contacts received during the first six months of 2020. Data on contacts related to violence were also available from 2019, and used as baseline. The media search used a combination of search terms to identify relevant articles and news stories published between March 1 and June 17, 2020. Overall, the number of contacts to child helplines seems to have drastically increased since the beginning of the pandemic. However, the number of contacts related to violence has increased in some countries, while it decreased in others. While a mixed picture emerges with respect to violence, the increase in overall contacts made to child helplines provides evidence that such services are a critical lifeline for many children and women during times of crisis. Child helplines should be strengthened; and child protection services should be designated as essential during emergencies to ensure children receive the support they need.